2019
DOI: 10.1111/evj.13117
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A and plasma fibrinogen concentrations in horses following emergency exploratory celiotomy

Abstract: Summary Background Acute‐phase proteins may help assess the nature and severity of lesions and outcome in horses undergoing colic surgery. Objectives To compare serum amyloid A and plasma fibrinogen concentrations ([SAA] and [fibrinogen]) in the immediate post‐operative period after exploratory celiotomy and determine their value in assessment of post‐operative complications and survival to discharge. Study design Observational study. Methods This study included horses over 1 year of age undergoing exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
2
20
1
3
Order By: Relevance
“…Serum amyloid A (SAA) has been examined in several papers to aid in the diagnosis of post‐operative colic complications. A new study examining SAA following exploratory celiotomy in 300 horses corroborated previous findings that SAA and fibrinogen concentrations in post‐operative colic cases were found to peak at 2 and 4 days post‐operatively respectively 15 . This study showed that SAA was elevated in horses with complications in the post‐operative period but that only SAA on day 5 could be used as a predictor of survival.…”
supporting
confidence: 81%
“…Serum amyloid A (SAA) has been examined in several papers to aid in the diagnosis of post‐operative colic complications. A new study examining SAA following exploratory celiotomy in 300 horses corroborated previous findings that SAA and fibrinogen concentrations in post‐operative colic cases were found to peak at 2 and 4 days post‐operatively respectively 15 . This study showed that SAA was elevated in horses with complications in the post‐operative period but that only SAA on day 5 could be used as a predictor of survival.…”
supporting
confidence: 81%
“…47 It is known that surgery itself, such as exploratory celiotomy for colic, causes an increase in APPs, including SAA. 43,[48][49][50] Compared with more minor surgical procedures, exploratory celiotomy causes a prolonged APR, with serum SAA concentrations increased from 48 to 96 hours after surgery (compared with 12-24 hours with minor procedures). 48,50,51 Horses with postoperative complications had a more pronounced increase in SAA (61.4-fold over baseline) and took longer to achieve peak values (96 hours) compared with horses without complications (29fold increase; peak at 48 hours).…”
Section: Gastrointestinal Disease and Serum Amyloid Amentioning
confidence: 99%
“…43,[48][49][50] Compared with more minor surgical procedures, exploratory celiotomy causes a prolonged APR, with serum SAA concentrations increased from 48 to 96 hours after surgery (compared with 12-24 hours with minor procedures). 48,50,51 Horses with postoperative complications had a more pronounced increase in SAA (61.4-fold over baseline) and took longer to achieve peak values (96 hours) compared with horses without complications (29fold increase; peak at 48 hours). 50 Another prospective study assessing SAA and complications in postoperative colic patients found that the magnitude of SAA increase was greater at 48 hours and 4 to 6 days postsurgery in horses with versus those without complications.…”
Section: Gastrointestinal Disease and Serum Amyloid Amentioning
confidence: 99%
See 1 more Smart Citation
“…This study by Michael De Cozar and colleagues in the UK aimed to compare serum amyloid A ([SAA]) and plasma fibrinogen ([fibrinogen]) concentrations in the immediate post‐operative period in horses undergoing exploratory celiotomy for colic unresponsive to medical management .…”
Section: Saa and Fibrinogenmentioning
confidence: 99%